Gender matters : female policymakers' influence in industrialized nations - O'Regan, Valerie R., 1956- (Praeger, 2000)
This is an examination of the relationship between female policymakers and policy outputs. The author's primary concern is whether or not female policymakers are associated with the advancement of ""women's issues"" in the policy realm.